Development of Web-Based Interactive Learning Media on Quadratic Equation Materials - M. Zainul Arifin; Abd. Qohar (EduMa: Mathematics education learning and teaching, 2024)
Web-based interactive learning media can help students in the learning process because of the easy access provided, one of which is by using Power Point and iSpring. The purpose of this research is to develop web-based interactive learning media containing quadratic equation material that is valid and practical so that it is useful for honing students' abilities in solving quadratic equation problems. The purpose of this research is to produce web-based interactive learning media that is suitable for the topic of quadratic equations, and uses a modified 4D development model consisting of three stages, namely determining objectives and strategies, designing products, and developing products. The data collected in this study were obtained through validation sheets and student questionnaires. After the validation process, peerteaching was carried out on several students. Based on the validity test results, the web-based interactive learning media on quadratic equation material has met the validity criteria. It is expected that this learning media can help students in learning quadratic equation material more interactively